About Local Rules of Law of Modern Russian Legislation - Vladimir Valentinovich Kozhevnikov (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2021)
This scientific article is devoted to the problems of local norms of modern Russian law: its features, necessity and classification. Attention is drawn to those local rules of law that must necessarily be in enterprises. It is noted that the scope of the former is not limited only to the scope of labor law.